Voltage‐gated sodium channel 1.7 expression decreases in dorsal root ganglia in a spinal nerve ligation neuropathic pain model - Ming Li; Shao‐Jin Zhang; Lin Yang; Xiao‐Lei Fang; Hao‐Fan Hu; Ming‐Yue Zhao; Lei Li; Yan‐Yan Guo; Jin‐Ping Shao (Kaohsiung Journal of Medical Sciences, 2019)
Abstract The role of the voltage‐gated sodium channel 1.7 (Nav1.7) is unclear in models of neuropathic pain induced by nerve injury. In the present study, we measured expression levels of Nav1.7 in two distinct neuropathic pain models: spinal nerve ligation (SNL) and chronic constriction injury (CCI). In the SNL model, both mRNA and protein levels of Nav1.7 were markedly lower in the L5 dorsal root ganglia (DRG) but were significantly higher in the L4 DRG. Nav1.7 protein levels were notably higher in both L4 and L5 DRGs under CCI conditions. We found that excessive damage of L5 nerves such as SNL reduced expression levels of Nav1.7 in the injured L5 DRG and activated the adjacent uninjured DRG, resulting in Nav1.7 level increases in the adjacent L4 DRG. We confirmed again that Nav1.7 was closely related to neuropathic pain induced by nerve injury. More importantly, our results suggest that tracing the molecular changes exclusively in the L5 DRG in SNL model may not completely explain the pain mechanism; it is necessary to study the adjacent uninjured L4 DRG.